Optogenetic evocation of field inhibitory postsynaptic potentials in hippocampal slices: a simple and reliable approach for studying pharmacological effects on GABAA and GABAB receptor-mediated neurotransmission - Dine, Julien; Kühne, Claudia; Deussing, Jan M.; Eder, Matthias (Frontiers in Cellular Neuroscience, 2014)
The GABAergic system is the main source of inhibition in the mammalian brain. Consequently, much effort is still made to develop new modulators of GABAergic synaptic transmission. In contrast to glutamatergic postsynaptic potentials (PSPs), accurate monitoring of GABA receptor-mediated PSPs (GABAR-PSPs) and their pharmacological modulation in brain tissue invariably requires the use of intracellular recording techniques. However, these techniques are expensive, time- and labor-consuming, and, in case of the frequently employed whole-cell patch-clamp configuration, impact on intracellular ion concentrations, signaling cascades, and pH buffering systems. Here, we describe a novel approach to circumvent these drawbacks. In particular, we demonstrate in mouse hippocampal slices that selective optogenetic activation of interneurons leads to prominent field inhibitory GABAAR- and GABABR-PSPs in area CA1 which are easily and reliably detectable by a single extracellular recording electrode. The field PSPs exhibit typical temporal and pharmacological characteristics, display pronounced paired-pulse depression, and remain stable over many consecutive evocations. Additionally validating the methodological value of this approach, we further show that the neuroactive steroid 5-THDOC (5 µM) shifts the inhibitory GABAAR-PSPs towards excitatory ones.